Da recorribilidade ao recurso: um caso emblemático do movimento processual. - Gouveia Filho, Roberto Pinheiro Campos (2020)
What is an appeal? It is a kind of intuitive question, not for those who are experts in procedural law, but also, and, especially, for those who act as agents of the procedural system. The answer, however, is not at all simple, it is enough to see that there is no unquestionable definition in proceduralistics of this, which is one of the most important concepts of law. This work intends to answer the question above. However, not in a way more suited to what is produced in Brazilian procedural law; without leaving from the scope of Legal Dogmatics, the concept of appeal will be analyzed from a movement perspective. That is: from the Aristotelian Conception of the transition from being in potency to being in action. The work to be developed, in no way, intends to review philosophical concepts. It is not a matter of doing philosophy; but to use this (in particular, the tributary to Aristotle) some of its fundamental concepts to establish a solid base for dogmatic study. In the legal perspective, the Legal Fact Theory is adopted as a theoretical framework, in the aspect attributed to Pontes de Miranda. The marriage between Aristotelian ontology and the Pontifical legal fact proves to be extremely adequate for the purpose of this thesis, because, among other things, it clarifies the concepts inherent to his idea. Hence the title of the thesis: “The power to recourse an appear”. Power, which, in the Pontifical perspective, takes on the appearance of a legal situation, precedes the act, which, in the same perspective, is a legal fact. Although it is one of these, the appeal, before being as such, is, at least in possibility, the legal situation that gives it conditions to be. This movement is almost entirely procedural, since both the power (the ability to appeal) and the act (the appeal) are generated in the process, understood as one of the possible legal areas. Hence the subtitle: “an emblematic case of the procedural movement”. However, something so particular seen from such a general perspective could not be directly analyzed: it is necessary, based on (more) universal concepts, which, as necessary, need to be explained, to obtain premises for the deduction. The thesis is, in short, a whole movement from the general to the (almost) particular.